Integrating Spirituality Into Treatment: Resources for Practitioners. 1999
DOI: 10.1037/10327-012
|View full text |Cite
|
Sign up to set email alerts
|

Serenity.

Abstract: TABLE 12.2 Defining Characteristics of Serenity~1. The ability to detach from desires and/or emotion and feelings. 2. The ability to be in touch with an inner haven of peace and security. 3. A sense of connectedess with the universe. 4. A trust in the wisdom of the universe. 5. The habit of actively pursuing all reasonable avenues for solving problems. 6. An ability to accept situations that cannot be changed. 7. A way to give unconditionally of one's self. 8. Forgiveness of self and others. 9. The ability to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 5 publications
(18 reference statements)
0
5
0
Order By: Relevance
“…You et al (2020) found that gratitude directly predicted prosocial behavior in adolescents. In addition, serenity is a feeling of peace and trust that can be experienced independently of external events and involves inner peace, even in the face of adverse events (Connors et al, 1999). Previous research has found that those who perceive themselves as more serene show higher levels of prosocial behaviors (Connors et al, 1999).…”
Section: Positive Emotion and Prosocial Behavior In Adolescentsmentioning
confidence: 99%
See 1 more Smart Citation
“…You et al (2020) found that gratitude directly predicted prosocial behavior in adolescents. In addition, serenity is a feeling of peace and trust that can be experienced independently of external events and involves inner peace, even in the face of adverse events (Connors et al, 1999). Previous research has found that those who perceive themselves as more serene show higher levels of prosocial behaviors (Connors et al, 1999).…”
Section: Positive Emotion and Prosocial Behavior In Adolescentsmentioning
confidence: 99%
“…In addition, serenity is a feeling of peace and trust that can be experienced independently of external events and involves inner peace, even in the face of adverse events (Connors et al, 1999). Previous research has found that those who perceive themselves as more serene show higher levels of prosocial behaviors (Connors et al, 1999). Finally, sympathy constitutes the affective component of empathy and is the ability to tune into the emotions of others and the inclination to help (Oros, 2014).…”
Section: Positive Emotion and Prosocial Behavior In Adolescentsmentioning
confidence: 99%
“…Acceptance and empathy are closely related, and each leads to the other. Acceptance is also an outcome of the spiritual concept of serenity, the acceptance of what one cannot change (Connors, Toscova, & Tonigan, 1999). Connors et al (1999) noted what seems to be a reciprocal relationship between extending acceptance to others and experiencing serenity oneself.…”
Section: Helping Categoriesmentioning
confidence: 99%
“…In Daoism, equanimity is more than just being comfortable with the situation; in fact, it is seen as a “calm, concentrated, unified state of consciousness as a means of experiencing inner peace and generating wisdom” (Gunaratana, 1985, p. 3), and this inner peace is independent of the external circumstances (Connors, Toscova, & Tonigan, 1999). This sense of equanimity is particularly important in individuals who are working in response to death-related matters.…”
Section: Discussionmentioning
confidence: 99%